2015
DOI: 10.1097/hjh.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin II on voltage-gated sodium currents in aortic baroreceptor neurons and arterial baroreflex sensitivity in heart failure rats

Abstract: Impairment of arterial baroreflex sensitivity is associated with mortality in patients with chronic heart failure (CHF). Elevation of plasma angiotension II (Ang II) contributes to arterial baroreflex dysfunction in CHF. A reduced number of voltage-gated sodium (Nav) channels in aortic baroreceptor neurons are involved in CHF-blunted arterial baroreflex. In this study, we investigated acute effect of Ang II on Nav currents in the aortic baroreceptor neuron and on arterial baroreflex in sham and coronary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Our recent study has also confirmed the involvement of Ang II in CHF-induced arterial baroreflex abnormality (Zhang et al, 2015 ). In our study, overexpression of the AT1R mRNA and protein and elevation of the local Ang II concentration in the NG from CHF rats were observed (Zhang et al, 2015 ).…”
Section: Angiotensin II Signaling Pathway and Reduced Activation Of Tsupporting
confidence: 81%
See 3 more Smart Citations
“…Our recent study has also confirmed the involvement of Ang II in CHF-induced arterial baroreflex abnormality (Zhang et al, 2015 ). In our study, overexpression of the AT1R mRNA and protein and elevation of the local Ang II concentration in the NG from CHF rats were observed (Zhang et al, 2015 ).…”
Section: Angiotensin II Signaling Pathway and Reduced Activation Of Tsupporting
confidence: 81%
“…Our recent study has also confirmed the involvement of Ang II in CHF-induced arterial baroreflex abnormality (Zhang et al, 2015 ). In our study, overexpression of the AT1R mRNA and protein and elevation of the local Ang II concentration in the NG from CHF rats were observed (Zhang et al, 2015 ). Additionally, local microinjection of losartan into the NG significantly improved CHF-attenuated arterial baroreflex sensitivity, whereas this drug did not change the arterial baroreflex sensitivity in sham rats.…”
Section: Angiotensin II Signaling Pathway and Reduced Activation Of Tsupporting
confidence: 81%
See 2 more Smart Citations
“…These signals are transmitted to the Nucleus Tractus Solitarius from which secondary projections arise for control of sympathetic and parasympathetic outflows 19 . Baroreceptor sensitivity is depressed in heart failure due to persistent enhancement of the sympathetic activity, possibly related to central angiotensin II levels 18, 77 . Impairment in baroreceptor sensitivity in heart failure is associated with increased mortality 30, 78, 79 .…”
Section: Introductionmentioning
confidence: 99%